SbbR/SbbA, an Important ArpA/AfsA-Like System, Regulates Milbemycin Production in Streptomyces bingchenggensis - He, Hairong; Ye, Lan; Li, Chuang; Wang, Haiyan; Guo, Xiaowei; Wang, Xiangjing; Zhang, Yanyan; Xiang, Wensheng (Frontiers in Microbiology, 2018)
Abstract Milbemycins, a group of 16-membered macrolide antibiotics, are used widely as insecticides and anthelmintics. Previously, a limited understanding of the transcriptional regulation of milbemycin biosynthesis has hampered efforts to enhance antibiotic production by engineering of regulatory genes. Here, a novel ArpA/AfsA-type system, SbbR/SbbA (SBI_08928/SBI_08929), has been identified to be involved in regulating milbemycin biosynthesis in the industrial strain S. bingchenggensis BC04. Inactivation of sbbR in BC04 resulted in markedly decreased production of milbemycin, while deletion of sbbA enhanced milbemycin production. Electrophoresis mobility shift assays (EMSAs) and DNase I footprinting studies showed that SbbR has a specific DNA-binding activity for the promoters of milR (the cluster-situated activator gene for milbemycin production) and the bidirectionally organized genes sbbR and sbbA. Transcriptional analysis suggested that SbbR directly activates the transcription of milR, while represses its own transcription and that of sbbA. Moreover, 11 novel targets of SbbR were additionally found, including seven regulatory genes located in secondary metabolite biosynthetic gene clusters (e.g. sbi_08420, sbi_08432, sbi_09158, sbi_00827, sbi_01376, sbi_09325 and sig24sbh) and four well-known global regulatory genes (e.g. glnRsbh, wblAsbh, atrAsbh and mtrA/Bsbh). These data suggest that SbbR is not only a direct activator of milbemycin production, but also a pleiotropic regulator that controls the expression of other cluster-situated regulatory genes and global regulatory genes. Overall, this study reveals the upper-layer regulatory system that controls milbemycin biosynthesis, which will not only expand our understanding of the complex regulation in milbemycin biosynthesis, but also provide a basis for an approach to improve milbemycin production via genetic manipulation of SbbR/SbbA system.